2015
DOI: 10.1161/circoutcomes.114.001244
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Paradox in Patients Hospitalized With Coronary Artery Disease or Acute Ischemic Stroke

Abstract: Despite the plethora of data exploring smokers' post-MI survival advantage, the role of cigarette smoking in the shortterm prognosis after AIS remains to be clarified, and analyses Background-Smoking is a potent risk factor for coronary artery disease (CAD) and acute ischemic stroke (AIS), but there are numerous reports of lower in-hospital mortality among smokers versus nonsmokers hospitalized for these events. Methods and Results-We analyzed all consecutive patients hospitalized with a first index CAD (n=158… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 43 publications
4
20
0
2
Order By: Relevance
“…The association of age with the occurrence of seizures after stroke is controversial with younger age shown as a risk factor for early seizures, while others have not shown such association [7,8]. The association of smoking with better functional outcome might be explained by the effect of confounding (as smokers tend to have strokes at younger ages and also fewer vascular risk factors) or a possible true association (“the smoking paradox”) [16]. However, this was not statistically significant (OR 0.55, 95% CI 0.27-1.12; p = 0.11).…”
Section: Discussionmentioning
confidence: 99%
“…The association of age with the occurrence of seizures after stroke is controversial with younger age shown as a risk factor for early seizures, while others have not shown such association [7,8]. The association of smoking with better functional outcome might be explained by the effect of confounding (as smokers tend to have strokes at younger ages and also fewer vascular risk factors) or a possible true association (“the smoking paradox”) [16]. However, this was not statistically significant (OR 0.55, 95% CI 0.27-1.12; p = 0.11).…”
Section: Discussionmentioning
confidence: 99%
“…Some prior studies, however, have suggested the existence of a “smoker's paradox,” implying that the outcomes of acute myocardial infarction (MI) may be more favorable in smokers than in nonsmokers 2, 3, 4, 5, 6. More recently, smoking has also been shown to be associated with lower in‐hospital mortality in patients with acute ischemic stroke, acute heart failure, and cardiac arrest 7, 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] More recently, smoking has also been shown to be associated with lower in-hospital mortality in patients with acute ischemic stroke, acute heart failure, and cardiac arrest. [7][8][9][10] This phenomenon of smoker's paradox was first introduced into scientific discourse >25 years ago, when studies in the prethrombolytic era showed that smokers with acute MI experienced lower mortality compared with nonsmokers. [3][4][5]11 Similar findings of paradoxical associations with smoking were also seen subsequently in randomized clinical trials investigating thrombolytic therapy for ST-segment elevation MI (STEMI).…”
mentioning
confidence: 99%
“…However, previous studies have shown that they seem to be associated with lower mortality after coronary artery disease or acute ischemic stroke. [25,26] Mechanisms of these paradoxes remain unclear.…”
Section: Discussionmentioning
confidence: 99%